Sanksi Pidana Terhadap Ujaran Kebencian (Hate Speech) - I Made Kardiyasa; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2020)
Hate speech in daily life people now such as expression, sedition, and provocation hate to other people and other community in many aspect such as religion, sex orientation, disabled, gender, racial , skin color, nationality and many else. If hate speech didn’t handle with effective way, efficient, and handle with corresponding with the valid law, so it can be impact social conflict that can increase discrimination action, violence and death loss. In this case there will be a bad impact which so danger for the hate speech victim, so in this case the writer’s get two solution to handle hate speech, that are protection law of hate speech victims and punishment criminal for the people who does hate speech. In this legal opinion writing, I am as a writer use normative method. In my experience, I do problem approach constitution which has related with hate speech, and then this research material reviewed. The result of this research is about law protective for the hate speech victims so that achievement can be protect them and the hate speech victims can feels safe. Hate speech can be says of criminal act because of what they have been done to hate speech victims. Unlawful actions that have been done with on propose or accidentally must be accounted for the acts that consist of constitution that happened and stated as acts that can be get a punishment in jail or fine. Ujaran kebencian dalam kehidupan manusia saat ini yang berupa ungkapan, hasutan, dan provokasi kebencian kepada seseorang atau suatu kelompok lain, dalam hal berbagai aspek berupa, agama, cacat, orientasi seksual, gender, ras, warna kulit, kewarganegaraan, dan lain-lain. Jika hate speech tidak di tangani dengan efektif, efesien dan ditangani sesuai hukum yang berlaku, bisa menimbulkan suatu dampak konflik sosial yang bisa memicu tindak diskriminasi, kekerasan dan atau penghilangan nyawa. Dengan timbulnya dampak yang sangat membahayakan bagi korban hate speech, maka penulis mendapatkan dua rumusan masalah dalam menangani hate speech yaitu, perlindungan hukum bagi korban hate speech dan sanksi pidana bagi pelaku hate speech. Penelitian ini mengunakan metode penulisan normative dan menggunakan pendekatan permasalahan perundang-undangan yang berkaitan dengan hate speech Kemudian bahan penelitian di kaji. Hasil dari penelitian berupa perlindungan hukum bagi korban hate speech supaya tercapainya rasa aman dan dapat melindungi bagi mereka yang menjadi korban hate speech. Hate speech dapat dikatakan sebagai tindak pidana karena telah melakukan suatu Tindakan melawan hukum yang dilakukan dengan sengaja ataupun dengan tidak sengaja harus dipertanggungkawabkan atas tindakannnya berdasarkan undang-undang yang berlaku dan dinyatakan sebagai tindakan yang dapat dihukum kurungan atau denda.